Pensamento crítico e World Englishes: um projeto de Aprendizagem Baseada na Investigação à luz da Teoria da Complexidade - Pereira, Eduarda Serpa (Universidade do Vale do Rio dos Sinos, 2021)
The critical thinking can be described as an ability of analyzing, reflecting, questioning beliefs or oneself, and even as a state of doubt (DEWEY, 1979). This ability can be developed through Active Methodologies (VIEIRA, 2017). In the field of Active Methodologies, there is the Inquiry-based Learning (IBL) approach which seeks to instigate the learner to be the protagonist of the learning process and to develop critical thinking skills (DEWEY, 1995; PEDASTE et. al., 2015). Furthermore, the IBL can be applied in the context of English as an Additional Language (PARASCHOPOULOU, 2018). On the other hand, in Brazil, the varieties that usually prevail in these educational environments are the British and American ones (FRANCESCON; SENEFONTE; BARONAS, 2013), leading to a homogenous and excluding view of language (SILVA, 2019). Considering that those learning environments, like the classroom, are complex systems, according to the Complexity Theory (LARSEN-FREEMAN, 2011), this dissertation objectifies to verify whether the Inquiry-based Learning approach, under a Complexity Theory perspective, can develop the critical thinking skills of students of English as an Additional Language through the contact with the English linguistic variation (World Englishes). In order to do that, we also seek to propose an analysis of the perception and reception of the students in relation to the Active Methodology IBL and of process of development of the students throughout the classes through the Complexity Theory; to give opportunity that students of English as an Addition Language can, through critical thinking and the work with the IBL, demonstrate a bigger knowledge and a higher esteem of the different World Englishes; and, to propitiate students of English as an Additional Language, through the contact and knowledge of other varieties, can come to esteem their own English variety. This qualitative research consists in an action research (TRIPP, 2005) carried out with students of English as an Additional Language from a language course, localized in the coal region of Rio Grande do Sul. To the data generation, a semi structured interview was conducted with 6 students from this institution, besides 8 classes about the World Englishes, through the IBL, which were recorded via video and audio, which were later transcribed. Besides that, the data generation consists of field diaries of the students and the teacher, who is also the researcher. Due to the moment of coronavirus pandemic, the data was generated exclusively through remote meetings, attended via a videoconference platform. Among the generated data analyzed, it was noted that the students developed higher sense of esteem about the World Englishes and their culture, as well as a resignification and acceptance of their own English and variety. It was also observed that the students reported positive perceptions about the IBL approach. The data still reveals a view of the classroom of Additional Languages as a complex system, in a way that each student developed in its uniqueness and particularity, through the interaction with the teacher, with other students and with the environment.
Keywords: Teoria da Complexidade; Aprendizagem Baseada na Investigação; Pensamento crítico; World Englishes; Complexity Theory; Inquiry-based Learning; Critical thinking; ACCNPQ::Lingüística, Letras e Artes::Lingüística